EVALUASI FUNGSI ESTETIKA, KENYAMANAN DAN KESELAMATAN JALUR HIJAU JALAN (STUDI KASUS JALAN PROF. ALI HASJMY) - Fakhrurradhi Fakhrurradhi; Muhammad Isya; Mirza Irwansyah (Prodi Magister Teknik Sipil Unsyiah, 2018)
The Green path in the road is the part of the landscape in the space area of the road which has safety and comfortability function to the road users, supporting education activities, recreation, conservation aesthetics, and area identity and become a character of a city. The plant is the main element in structuring the green road path. The plant functions on the road landscapes are to reduce exposure to direct sunlight and vehicle lights, as a director, physical barrier, movement control, microclimate controller, and wildlife habitat. The arrangement of plant placement in the green path in the area belong to the road likes tree, shrubs which by the principal and regulation of design will deliver more impact regarding aesthetics. This research purpose is to conduct the assessment against trees planting in the green path of the road regarding aesthetic, comfort and safety, effectively to support the layout of Banda Aceh city. Identifying technical incompatibility of tree planting that occurs on the green path of the road and also the need of strategy determine the implementation of the green path of the road.The purpose of this research is to identify the placement of tree on green road path and define the implementation strategy on the implementation of green road path by using a qualitative descriptive method which is supported by perceptions of officials and expert respondents. Sources of data to be used in this study are primary data and secondary data. The analysis result obtained three alternative strategies that is 1) Increase the quantity and quality of trees and improving the planting systems regulation, spacing, and tree species (type). 2) Improve the socialization of green open space masterplan of Banda Aceh city and technical regulations of green road path to utilize open space in space belong to the road and road monitoring room. 3) Increase community participation and support and related parties in creating a systematic green road path according to Green Open Space master plan and technical regulation of green road path